Analisis Perbandingan Indeks Kemiripan Tanah pada Topsekuens Granit Gunung Sirimau Kota Ambon - Umanailo, Irmanji; Risamasu, Robby G; Puturuhu, Ferad; Luhukay, Marcus (JURNAL PERTANIAN KEPULAUAN, 2025)
This study aims to identify and describe soil morphological traits in the granite toposequence and analyze these traits to assess the similarity index between soil profiles. This study used a survey method involving transect observations and complete profile observations. Variable soil observations were made in a downward direction, following each change in slope segment on the granite toposequence. The results showed that Cambisol (Dystrudepts) soils developed with physical and chemical properties on three profiles for soil color ranging from yellowish brown to brownish yellow and yellowish red to red. The soil texture ranges from loamy sand to dusty clay, and the soil structure is rounded cubical. The soil has an acidic to slightly acidic pH and a slightly sticky consistency when moist and very low to low C-organic content. The similarity index assessed in the three profiles includes parameters such as dust/clay ratio, pH H₂O, and C-organic, which are very similar due to the similarity of the constituent rock formations.